PHENOLIC CONTENTS, ANTIBACTERIAL AND ANTIOXIDANT ACTIVITIES OF FLOWER, LEAF AND STEM EXTRACTS OF FERULAGO ANGULATA (SCHLECHT) BOISS - Azarbani, Farideh; Saki, Zeinab; Zareei, Ali; Mohammadi, Abdolnasser (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Ferulago angulata known as Chavir is an Iranian endemic plant that has been used as the food preservative and natural flavor since long times. In the present study, antibacterial and antioxidant activities of aqueous and methanol extracts from flower, leaf and stem of F. angulata (Schlecht.) Boiss from Lorestan Province of Iran were evaluated. Total phenol, flavonoid and anthocyanin contents were also determined. Methods: Antibacterial activity was studied by disc diffusion method. Diphenylpicrylhydrazyl (DPPH) assay was used to determine the antioxidant property. The total phenol, flavonoid and anthocyanin contents were measured by Folin Ciocalteu, AlCl3 and pH differential methods, respectively. Results: None of the sample extracts showed significant antibacterial activity against tested pathogens. All extracts had inhibitory activity on DPPH radicals with concentration-dependent manner. IC50 values ranged from 214±8.2 to 1606±94.4 µg/ml. The total phenol, flavonoid and anthocyanin contents were in the range of 59±0.017 to 483.5±0.098 mg of Gallic acid equivalents per g of dried extract, 0.5±0.004 to 539±0.29 mg of Quercetin equivalents per g of dried extract and 0.43±0.02 to 4.2±0.82 mg Cyanidin-3-glucoside, respectively. Conclusion: The Flower aqueous extract exhibited the maximum phenolic compounds and antioxidant activity but, the stem methanol extract was the weakest one.